Situation Report: Romania, 23 May 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Two Romanian Party Secretaries Get Provincial Posts Romanian Media Discuss Environmental Pollution and Conservation Logistics Support for the Merchant Fleet in 1973 Foreign-Language Broadcasts for Listeners Abroad First Italian-Romanian Mixed Society Set Up Improvements in Curricula in Foreign Trade Education Proposed Discussions on the Program for the Development of Higher Education Reorganization of Ministries and Economic Units